Effects of Salinity and Drought Stress on Seed Germination of Common Purslane (Portulaca oleracea) - Anh Cong Pham; Tuan Chau Vo; Hoang Duc Vu; Dan Quang Tran (Biology and Life Sciences Forum, 2023)
Common purslane (Portulaca oleracea) is a halophyte, consumed not only as an edible vegetable but also as a traditional medicine. This plant can adapt to extreme salinity and drought conditions and their effects on plant growth, yield and quality were elucidated, but the effects on seed germination was still unclear. Seed germination is an important stage for establishing P. oleracea seedlings that contribute to plant yield and productivity. Thus, the objective of the present study was to examine the individual effects of salinity and drought stress at different levels on the characteristics of seed germination, which the seeds suffered from −0.22, −0.45, −0.89, and −1.78 MPa osmotic stresses induced by polyethylene glycol (PEG), or from 50, 100, 200, and 400 mM NaCl stresses with equivalent osmotic pressures. The seeds sown in petri dishes containing filter paper layers that were flooded with NaCl or PEG-6000 solutions for the treatments and germination parameters were determined daily for 15 days. Data showed that germination percentage (GP), germination rate (GR), germination energy (GE), and mean germination time (MGT) were significantly decreased with increasing levels of salt and osmotic stresses, suggesting that the salinity and drought stress reduced the germination capability of seeds. Moreover, the seeds maintained germination with PEG osmotic pressure above −0.22 MPa, but not with NaCl concentration greater than 50 mM that induced a similar osmotic pressure, suggesting that the ion toxicity effect on the seed germination might be higher than the osmotic effects.